The Acceptability of Physiotherapy Care in Emergency Departments: An Exploratory Survey of Emergency Department Physicians - Matifat, Eveline; Lavoie-Côté, Pascale; Kounda, Nabila; Charrier, Lorie; Perreault, Kadija; Desmeules, François (Journal of Research in Interprofessional Practice and Education)

(untitled) (Canadian Institute for Studies in Publishing Press (Simon Fraser University at Harbour Centre), 2021)
Background: Interprofessional emergency department (ED) models of care, including physiotherapists, have emerged to answer growing demands for ED care. The purpose of this study was to assess the perceptions of ED physicians regarding ED physiotherapy.Methods and findings: Ninety-five ED physicians, members of one of two ED physicians’ associations in the province of Québec, completed a survey (response rate = 14.7%). Most had a positive perception of physiotherapists’ competencies (96.8%) and were confident that ED physiotherapy care is safe and efficient (96.8%).Conclusions: Based on responses from this limited sample, ED physicians have a positive perception of ED physiotherapy models of care.